1994
DOI: 10.1177/0148607194018002128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glutamine on Phagocytosis and Bacterial Killing by Normal and Pediatric Burn Patient Neutrophils

Abstract: Glutamine is essential for the function of lymphocytes and macrophages, where it serves, among other things, as a source of energy. Little information is available concerning the fuel that polymorphonuclear cells use for their metabolic and bactericidal functions. It was the purpose of this study to determine whether glutamine would enhance the in vitro bactericidal function of normal neutrophils and whether the amino acid would restore the observed impaired function in burn patients to or above the normal lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(66 citation statements)
references
References 13 publications
(5 reference statements)
4
58
1
3
Order By: Relevance
“…Glutamine plays an important role in protein (as amino-acid source), lipid (through NAD(P)H production) and nucleotide synthesis (through purine and pyrimidine production), and in NADPH oxidase activity (Newsholme et al 2003, Curi et al 2005. Glutamine raises the in vitro bacterial killing activity and the rate of ROS production by neutrophils (Ogle et al 1994, Pithon-Curi et al 1998. Pithon-Curi et al (2003) showed that glutamine has a protective effect on neutrophil apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine plays an important role in protein (as amino-acid source), lipid (through NAD(P)H production) and nucleotide synthesis (through purine and pyrimidine production), and in NADPH oxidase activity (Newsholme et al 2003, Curi et al 2005. Glutamine raises the in vitro bacterial killing activity and the rate of ROS production by neutrophils (Ogle et al 1994, Pithon-Curi et al 1998. Pithon-Curi et al (2003) showed that glutamine has a protective effect on neutrophil apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In rodent and human models, Gln is important for the synthesis of cytokines (e.g. IL-1b and IL-6) in macrophages and monocytes, phagocytosis and the production of reactive oxygen intermediates (Wallace and Keast, 1992;Ogle et al, 1994;Yassad et al, 1997). Lymphocytes utilize Gln primarily for cell division and lactate production (Newsholme et al, 1985;Newsholme et al, 1999).…”
Section: Glnmentioning
confidence: 99%
“…Macrophage-mediated phagocytosis is influenced by glutamine availability (11). Beneficial effects of the provision of glutamine (16) or its precursors (17) have been reported in patients submitted to surgery, radiation treatment or bone marrow transplantation or suffering from injury, sepsis or burns (18).…”
Section: Role Of Glutamine In Immune Functionmentioning
confidence: 99%